Characterization of a liquid-core waveguide cell for studying the chemistry of light-induced degradation. Issue 10 (7th April 2021) - Groeneveld, Iris; Schoemaker, Suzan E.; Somsen, Govert W.; Ariese, Freek; van Bommel, Maarten R.
Abstract : A gas permeable liquid core waveguide (LCW) was successfully used for the simulation and in situ spectroscopic analysis of the photodegradation processes of the two dyes crystal violet and eosin Y. Abstract : Many organic compounds undergo changes under the influence of light. This might be beneficial in, for example, water purification, but undesirable when cultural-heritage objects fade or when food ingredients ( e.g., vitamins) degrade. It is often challenging to establish a strong link between photodegradation products and their parent molecules due to the complexity of the sample. To allow effective study of light-induced degradation (LID), a low-volume exposure cell was created in which solutes are efficiently illuminated (especially at low concentrations) while simultaneously analysed by absorbance spectroscopy. The new LID cell encompasses a gas-permeable liquid-core waveguide (LCW) connected to a spectrograph allowing collection of spectral data in real-time. The aim of the current study was to evaluate the overall performance of the LID cell by assessing its transmission characteristics, the absolute photon flux achieved in the LCW, and its capacity to study solute degradation in presence of oxygen. The potential of the LID set-up for light-exposure studies was successfully demonstrated by monitoring the degradation of the dyes eosin Y and crystal violet.